Guideline for referral of patients with suspected lung cancer by family physicians and other primary care providers - Del Giudice, M. Elisabeth (College of Family Physicians of Canada, 2014)
OBJECTIVE: The aim of this guideline is to assist FPs and other primary care providers with recognizing features that should raise their suspicions about the presence of lung cancer in their patients. COMPOSITION OF THE COMMITTEE: Committee members were selected from among the regional primary care leads from the Cancer Care Ontario Provincial Primary Care and Cancer Network and from among the members of the Cancer Care Ontario Lung Cancer Disease Site Group. METHODS: This guideline was developed through systematic review of the evidence base, synthesis of the evidence, and formal external review involving Canadian stakeholders to validate the relevance of recommendations. REPORT: Evidence-based guidelines were developed to improve the management of patients presenting with clinical features of lung cancer within the Canadian context. CONCLUSION: Earlier identification and referral of patients with lung cancer might ultimately help improve lung cancer morbidity and mortality. These guidelines might also be of value for informing the development of lung cancer diagnostic programs and for helping policy makers to ensure appropriate resources are in place.